Preserving Cultural Knowledge through Community-Led MOOCs - Narayanan, Kulathu Ramaiyer; Poline, Bala; Amit, Pariyar; Chuah, Kee Man; Jaya Laxshmi, Meenatchisundaram (IPSI BgD, 2020)
Kulathuramaiyer, Narayanan & Pariyar, Amit & Bala, Poline & Laxshmi, Jaya & Chuah, Kee-Man. (2020). Preserving Cultural Knowledge through Community-Led MOOCs. 16. MOOCs have cultured a knowledge exchange phenomenon at a global scale making its strong presence in developing countries to pursue certain development goals, particularly to serve the rural indigenous communities. The current MOOC model, however tends to be inhibitive when it comes to integrating the complex realities of the under-served communities and their way of life. The growing commercial interests, increasing corporate partnerships, the ‘outside in’ course focus, one-way knowledge transfer, threats to local knowledge and decontextualized innovation are some aspects that questions its relevance to serve a social purpose. This paper aggregates the inadequacies of the current linear model of MOOC with a function model and exemplifies our ‘Community-Led MOOCs’ as a model to preserve cultural knowledge. The novel case of preserving the knowledge on threading and stringing Kelabit beads provides a compelling evidence that intergenerational knowledge sharing can be reestablished by giving the community the center stage in producing MOOCs and connecting the youths to the elderly population.